KONTRIBUSI PENDAPATAN USAHA PUPUK ORGANIK TERHADAP TOTAL PENDAPATAN KELOMPOK PADA SISTEM INTEGRASI PADI–TERNAK SAPI POTONG - Irvan, Aslina Asnawi; St. Rohani (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. In general farm and agriculture integrated (Crop-Livestock Systems), waste management feces and urine into organic products have not been pursued to the fullest to become a commercial product. The study aims to determine the income of rice- cattle integration system and determine thecontribution revenue of organic fertilizer made by farmers group mmassangang. The research was conducted in May-September 2014 housed in farmers group Ammassangang Ammassangang Village, District Lanrisang, Pinrang Regency. Type of research is quantitative descriptive. Analysis of the data used is descriptive statistical analys to calculate the average income. Results showed that the income earned by the farmer groups Ammassangang on business integration cattle grains obtained from three activities, namely organic fertilizer business, the cattle business, and the business of rice. Operating revenues cattle Rp. 16.871.500,- per month, businesses rice Rp. 17.966.620.- per month andorganic fertilizer business is Rp. 37.871.500, - per month. Contribution of organic fertilizer business income to total income of farmers group Ammassangang is 51.8% so it can be categorized as a branch of business. From this study can be explained that the organic fertilizer business gives substantial contribution to the total income farmers group Ammassangang, so this is an impact on improving the welfare of members of farmers group Ammassangang be an additional source of income.